Hard carbon composite material, preparation method and application thereof, and battery

By preparing hard carbon composite materials with rich microporous structure, the problems of low recycling rate of waste phenolic resin and high cost of negative electrode materials of sodium ion batteries are solved, and the high performance sodium storage capacity and first-week efficiency of sodium ion batteries are improved.

CN119320129APending Publication Date: 2025-01-17SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411651851.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The problem of low recycling rate of waste phenolic resin recycling, high cost of negative electrode materials of sodium ion batteries and low capacity, and low first-term efficiency.

Method used

By preparing waste phenolic resin into a hard carbon composite material with rich microporous structure, pre-carbonization, alkali activation and carbonization are used to form a hard carbon composite material with a high specific surface area, and carbon coating is carried out by chemical vapor deposition method , a closed-cell structure is formed to improve sodium storage capacity and first-week efficiency.

Benefits of technology

The high-value recycling of waste phenolic resin is realized, the cost of the negative electrode material of sodium ion battery is reduced, and the electrochemical performance of the battery is improved, including sodium storage capacity and first effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320129A_ABST
    Figure CN119320129A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon composite material, a preparation method and application thereof and a battery. The preparation method of the hard carbon composite material comprises the following steps: S1, heating waste phenolic resin for pre-carbonization to obtain a first precursor; the temperature rise rate of heating is 1-4 DEG C / min; s2, under a heating condition, performing alkali activation on the first precursor to obtain a second precursor; the temperature rise rate of heating is 1-4 DEG C / min; s3, carbonizing the second precursor to obtain a third precursor; and S4, carrying out carbon coating on the third precursor to obtain the hard carbon composite material. The battery assembled by the hard carbon composite material has excellent sodium storage capacity and first-week efficiency, realizes low-cost recovery and high-valued cyclic utilization of waste phenolic resin, and promotes large-scale production and preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon composite material and a preparation method, application and battery thereof. Background Art

[0002] At present, the extensive use of traditional energy sources such as coal, oil and natural gas based on fossil fuels is one of the causes of environmental pollution. Therefore, the development and research of clean, safe and sustainable new energy has become one of the basic strategies for coordinating energy and environment. Electrochemical energy storage (EES) is a mature energy system with high energy and power density. Its application has the advantages of portability and cleanliness, and is an important direction for the development of new energy technology.

[0003] Sodium-ion batteries are more suitable for renewable energy storage and grid-scale energy storage than lithium-ion batteries due to their advantages such as high natural abundance of metallic sodium, environmental friendliness, low price, and high safety. Graphite, as a commercial lithium-ion battery negative electrode material, performs poorly in sodium-ion batteries. The development of high-performance negative electrode materials is the key to the large-scale application of sodium-ion batteries. Hard carbon is considered to be one of the ideal negative electrode materials for sodium-ion batteries because of its large interlayer spacing and nanopores. Its wide source of raw materials makes it the most likely negative electrode material for sodium-ion batteries to achieve large-scale commercialization. At present, the precursor raw materials that can be used as hard carbon include coal-based, asphalt-based, biomass-based, resin-based and other types. The resin-based precursor is synthesized from the perspective of molecular cross-linking polymerization, and its molecular structure is easy to control. The product purity is higher than that of coal-based and asphalt-based, but its price is relatively higher than other precursors, and it is not easy to meet the low-cost requirements of sodium-ion battery negative electrode materials.

[0004] The rapid development of polymer technology has made polymer resin materials play an important role in people's lives. Phenolic resin insulation board is a closed-cell hard thermosetting resin material made of phenolic resin, flame retardant, smoke suppressant, curing agent, foaming agent and other additives. However, environmental influences such as heat, moisture, and ultraviolet radiation will cause the resin material to age and become solid waste. Since thermosetting phenolic resin insulation board has the characteristics of high strength, high hardness, insolubility and inmeltability, it is difficult to degrade in nature. Direct abandonment, landfill or incineration will cause serious environmental pollution. The lack of effective recycling technology makes the waste phenolic resin not only cause environmental pollution, but also a huge waste of resources. How to turn waste into treasure and realize the high-value utilization of waste phenolic resin is the current research hotspot. Summary of the invention

[0005] In order to solve the problems of low recycling rate of waste phenolic resin recyclate, high cost of negative electrode materials for sodium ion batteries, low capacity and low first efficiency, the present invention proposes a hard carbon composite material and its preparation method, application and sodium ion battery. The preparation method of the present invention prepares waste phenolic resin into a hard carbon composite material with rich microporous structure, which can not only realize the high-value recycling of waste phenolic resin, but also meet the demand of reducing the cost of negative electrode materials for sodium ion batteries, and the sodium ion battery using the hard carbon composite material can take into account both excellent sodium storage capacity and first cycle efficiency.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] The present invention provides a method for preparing a hard carbon composite material, which comprises the following steps:

[0008] S1, heating the waste phenolic resin for pre-carbonization to obtain a first precursor; the heating rate is 1-4°C / min;

[0009] S2. Under heating conditions, alkali-activating the first precursor to obtain a second precursor; the heating rate is 1-4°C / min;

[0010] S3, carbonizing the second precursor to obtain a third precursor;

[0011] S4. Carbon-coating the third precursor to obtain a hard carbon composite material.

[0012] In the present invention, in step S1, preferably, before pre-carbonization, the following steps may also be included:

[0013] Step S0, crushing, washing and drying the waste phenolic resin recovery material to obtain the waste phenolic resin.

[0014] The crushing equipment may be conventional equipment in the art, such as a claw knife crusher, a blade knife crusher or a flat knife crusher, preferably a blade knife crusher.

[0015] Wherein, the cleaning can be conventional in the art, such as mechanical stirring cleaning or ultrasonic cleaning, preferably ultrasonic cleaning. Further, the power range of the ultrasonic cleaning is 8000~14000Hz, preferably 11000Hz. Further, the temperature range of the ultrasonic cleaning is 40~70℃, preferably 55℃. Further, the time range of the ultrasonic cleaning is 0.5~3h, preferably 1h.

[0016] The drying method may be conventional in the art, for example, convection drying and / or conduction drying, preferably convection drying. Further, the convection drying temperature may be 80-120° C., preferably 105° C. Further, the convection drying time may be 1-10 hours, preferably 3-8 hours, for example 4 hours.

[0017] In the present invention, the waste phenolic resin recyclate may be conventional, commercially available waste phenolic resin in the art, such as waste phenolic resin insulation board and the like.

[0018] In the present invention, the waste phenolic resin recyclate may have at least one of the following parameters: ① ash content <2wt%; ② volatile matter <30wt%; ③ residual carbon value is 40~70wt%. Wherein, wt% means: the unit of weight percentage, indicating the proportion of a substance in a mixture. Specifically, the meaning of ash content is: the weight ratio of the residue of the dried waste phenolic resin recyclate burned to constant weight at 850±20℃ under air conditions to the original sample. The meaning of volatile matter is: under air-tight conditions, the waste phenolic resin recyclate is heated at 900±10℃ for 7 minutes, and the organic matter therein is decomposed by heat to produce a part of liquid (at this time in steam state) and gaseous products with smaller molecular weight, and this part of the product accounts for the proportion of the waste phenolic resin recyclate. The meaning of residual carbon value is: under air-tight conditions, the mass of coke generated after thermal decomposition at 550℃ accounts for the weight ratio of the original sample.

[0019] In the present invention, in step S1, the particle size of the waste phenolic resin may be 2 to 10 cm, preferably 3 to 5 cm.

[0020] In the present invention, in step S1, the pre-carbonization refers to a method of performing heat treatment at a relatively low temperature to carbonize the material to a certain extent.

[0021] In the present invention, in step S1, the pre-carbonization temperature may be 400-800°C, such as 650°C, 700°C or 750°C.

[0022] In the present invention, in step S1, the pre-carbonization time may be 1 to 5 hours, such as 2 hours, 3 hours or 4 hours.

[0023] In the present invention, in step S1, the heating temperature rise rate can be 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min. The heating temperature rise rate means the heating temperature rise rate during the process of heating to the pre-carbonization temperature.

[0024] In the present invention, in step S1, the pre-carbonization can be performed under an inert atmosphere, which generally refers to an atmosphere formed by a gas that does not react with the raw material when heated, and is not limited to an atmosphere formed by an inert gas. Further, the inert atmosphere can be argon or nitrogen, such as nitrogen.

[0025] In the present invention, in step S1, the pre-carbonization equipment may be conventional equipment in the art, such as a drum furnace, a box furnace, a rotary kiln or a pit furnace, such as a drum furnace.

[0026] In the present invention, in step S1, the pre-carbonization further includes a crushing step. Further, the crushing is to crush the product after the pre-carbonization cooling to obtain the first precursor. Further, the crushing equipment can be conventional equipment in the field, which can be a roller mill, a mechanical mill, a jet mill or a cryogenic mill, preferably a jet mill.

[0027] In the present invention, in step S1, the D of the first precursor 50 The particle size may be 3 to 10 μm, preferably 5 to 7 μm.

[0028] In the present invention, in step S2, the temperature of the alkali activation may be 600-900°C, preferably 700-800°C, for example 750°C.

[0029] In the present invention, in step S2, the alkali activation time may be 1 to 5 hours, such as 2 hours, 3 hours or 4 hours.

[0030] In the present invention, in step S2, the heating temperature rise rate is 3°C / min. The heating temperature rise rate refers to the heating temperature rise rate in the process of heating to the alkali activation temperature.

[0031] In the present invention, in step S2, the alkali activation can be performed under an inert atmosphere, which generally refers to an atmosphere formed by a gas that does not react with the raw material when heated, and is not limited to an atmosphere formed by an inert gas. Further, the inert atmosphere can be a nitrogen atmosphere, an argon atmosphere, or a helium atmosphere, preferably a nitrogen atmosphere.

[0032] In the present invention, in step S2, the alkali activation operation may include: heating the precursor material including the first precursor and the alkali compound to perform alkali activation.

[0033] The alkaline compound may be one or more of potassium bicarbonate, potassium ethyl oxalate, potassium oxamate and potassium hydrogen phosphate, for example, potassium ethyl oxalate, oxamate, potassium bicarbonate or potassium bicarbonate.

[0034] Wherein, the mass ratio of the first precursor to the alkaline compound may be 1:(0.1-1), for example, 1:0.5, 1:0.6 or 1:0.8.

[0035] In some preferred embodiments, the method for preparing the precursor material comprising the first precursor and the alkali compound comprises: mixing an aqueous solution of the alkali compound with the first precursor, stirring, and drying.

[0036] The mass ratio of the alkali compound to water in the alkali compound aqueous solution may be 1:(1-10), preferably 1:(2-10), such as 1:2, 1:3, 1:4 or 1:5.

[0037] The mixing temperature may be 20-40°C, preferably 25-35°C, for example 30°C.

[0038] The mixing time may be 0.5 to 4 hours, preferably 1 to 3 hours, for example 2 hours.

[0039] The drying temperature may be 100-120°C, preferably 100-110°C, for example 105°C.

[0040] The drying time may be 2 to 12 hours, preferably 4 to 10 hours, for example 8 hours.

[0041] In the present invention, in step S2, a washing step may be further included after the alkali activation, wherein the washing step is to wash the first precursor after the alkali activation to remove the residual salt therein.

[0042] Wherein, the washing may include acid washing and water washing steps in sequence.

[0043] The acidic solution used for pickling may be one or more of hydrochloric acid solution, phosphoric acid solution, nitric acid solution, sulfuric acid solution, acetic acid solution and formic acid solution, such as acetic acid solution.

[0044] The concentration of the acidic solution may be 0.5-6 mol / L, preferably 1-5 mol / L, for example 3 mol / L.

[0045] The stirring time of the pickling may be 1 to 10 hours, preferably 2 to 8 hours, for example 3 hours.

[0046] Wherein, the water washing adopts deionized water washing until the solution is neutral.

[0047] Generally, after the washing is completed, a drying step may be conventionally included, and the second precursor may be obtained after the drying.

[0048] The drying temperature may be 100-120°C, preferably 100-110°C, for example 105°C.

[0049] The drying time may be 2 to 12 hours, preferably 4 to 10 hours, for example 8 hours.

[0050] In the present invention, in step S3, the carbonization may be graded carbonization.

[0051] In some preferred embodiments, the graded carbonization includes a first carbonization and a second carbonization, the first carbonization is performed at a temperature of 500-800°C, and the second carbonization is performed at a temperature of 1100-1600°C.

[0052] The first carbonization temperature is, for example, 680°C, 700°C or 720°C.

[0053] The second carbonization temperature is, for example, 1300°C, 1400°C or 1500°C.

[0054] The heat preservation time of the first carbonization may be 1 to 6 hours, for example, 2 hours, 3 hours, 4 hours or 5 hours.

[0055] The second carbonization heat preservation time may be 1 to 6 hours, such as 2 hours, 3 hours or 4 hours. The carbonization heat preservation time refers to the heat preservation time at the carbonization temperature.

[0056] The heating rate of the first carbonization may be 2-10°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min. The heating rate of the first carbonization refers to the heating rate during the process of heating the temperature to the first carbonization temperature.

[0057] The heating rate of the second carbonization may be 1-10°C / min, such as 1°C / min, 2°C / min or 3°C / min. The heating rate of the second carbonization refers to the heating rate during the process of heating the temperature from the first carbonization temperature to the second carbonization temperature.

[0058] In the present invention, in step S3, the carbonization can be performed under an inert atmosphere. The inert atmosphere generally refers to an atmosphere formed by a gas that does not react with the raw material when heated, and is not limited to an atmosphere formed by an inert gas.

[0059] Furthermore, the inert atmosphere may be argon or nitrogen, for example nitrogen.

[0060] In the present invention, in step S3, the carbonization equipment is conventional in the art, such as a pit furnace, a rotary furnace, a tube furnace, a box furnace, a tunnel kiln, a vacuum furnace, a push plate kiln or a roller kiln, such as a box furnace.

[0061] In the present invention, in step S4, the carbon coating method can be conventional in the art, preferably a chemical vapor deposition method.

[0062] In some preferred embodiments of the present invention, in step S4, chemical vapor deposition is used for carbon coating, including the following steps: introducing an organic carbon source into a device containing the third precursor to perform a vapor deposition reaction.

[0063] The organic carbon source may be one or more of n-hexane, cyclohexane, thiophene, acetylene, ethylene, propylene, methane and propane, such as methane or propane, such as methane and acetylene.

[0064] The gas flow rate of the organic carbon source may be 5 to 100 mL / min, preferably 10 to 80 mL / min, such as 50 mL / min, 60 mL / min or 70 mL / min.

[0065] The carrier gas of the organic carbon source may be argon and / or nitrogen, for example nitrogen.

[0066] The gas flow rate of the carrier gas may be 20 to 500 mL / min, preferably 50 to 300 mL / min, for example, 150 mL / min.

[0067] The reaction temperature of the vapor deposition reaction may be 500-1000°C, preferably 650-950°C, such as 800°C, 850°C or 900°C.

[0068] The reaction time of the vapor deposition reaction may be 4 to 15 hours, preferably 5 to 10 hours, such as 6 hours, 7 hours or 8 hours.

[0069] The heating rate of the vapor deposition reaction may be 1-15°C / min, preferably 3-10°C / min, such as 5°C / min or 7°C / min. The heating rate refers to the heating rate of heating to raise the temperature to the temperature of the vapor deposition reaction.

[0070] The equipment used in the chemical vapor deposition method may be a rotary furnace, a fluidized bed or a tubular furnace, such as a rotary furnace.

[0071] The present invention provides a hard carbon composite material prepared by adopting the preparation method of the hard carbon composite material.

[0072] In the present invention, the hard carbon composite material comprises, from the inside to the outside, a core and a coating layer; the core comprises a porous carbon material, and the coating layer is a carbon layer.

[0073] In the present invention, the specific surface area of ​​the hard carbon composite material can be 1 to 10 m 2 / g, preferably 2~4 m 2 / g, for example 3.4 m 2 / g, 3.7 m 2 / g, 3.2 m 2 / g, 3.9 m 2 / g or 2.8m 2 / g.

[0074] In the present invention, the hard carbon composite material has a microporous structure, and the pore size of the micropores may be 0.3-1.5 nm, preferably 0.4-1.0 nm, such as 0.53 nm, 0.75 nm or 0.83 nm.

[0075] The present invention provides a use of the hard carbon composite material as described above as an electrode material in a battery.

[0076] Wherein, the electrode material is preferably a negative electrode material.

[0077] The present invention also provides a battery, which comprises the hard carbon composite material.

[0078] In the present invention, the battery is preferably a sodium ion battery.

[0079] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0080] The reagents and raw materials used in the present invention are commercially available.

[0081] The positive and progressive effects of the present invention are:

[0082] 1. The present invention realizes the high-value recycling of waste phenolic resins, solves the problem of high cost of raw materials for negative electrode materials of sodium ion batteries; through the synergistic effect between the various process steps, it realizes the effective regulation of relevant parameters such as the pore structure and specific surface area of ​​the hard carbon composite material, thereby improving the electrochemical performance of the resulting battery.

[0083] 2. The present invention etches the carbon skeleton with the help of alkali activation. By adjusting the amount of alkali compounds, the pore structure of the hard carbon composite material precursor is regulated, which is conducive to the formation of more microporous structures; and only appropriate amounts of acid washing and water washing are required to remove residual potassium-based substances and obtain pure carbon materials.

[0084] 3. The present invention coats the hard carbon composite material precursor by vapor deposition of carbon source, which can effectively regulate the pore structure and specific surface area of ​​the negative electrode material, forming more closed-pore structures that are conducive to sodium storage in the platform area, thereby improving the initial efficiency of the material (all above 85%). BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 This is a pore size distribution diagram of the hard carbon composite material obtained in Example 1 of the present invention.

[0086] Figure 2 This is a SEM morphology image of the hard carbon composite material obtained in Example 1 of the present invention.

[0087] Figure 3 This is a charge and discharge curve diagram of the hard carbon composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0088] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0089] Example 1

[0090] S0: 20kg of the purchased waste phenolic resin recycling (ash content is 0.8wt%, volatile content is 27wt%, residual carbon value is 68wt%) is crushed into particles of 3~5cm in size by a blade crusher, and then placed in an ultrasonic cleaning tank for ultrasonic cleaning. The ultrasonic cleaning power is 11000Hz, the ultrasonic cleaning water temperature is 55℃, and the cleaning time is 1h. After cleaning, it enters the convection drying system and is dried at 105℃ for 4h to obtain the waste phenolic resin.

[0091] S1: The waste phenolic resin obtained in S0 is placed in a drum furnace. Under nitrogen protection, the temperature is raised to 650°C at a rate of 2°C / min and kept constant for 4 h for pre-carbonization treatment. The material is discharged after naturally cooling to room temperature. Then it is crushed by a jet mill to make D50 about 6μm to obtain the first precursor.

[0092] S2: Weigh the first precursor and potassium ethyl oxalate in a mass ratio of 1:1, and weigh water in a mass ratio of potassium ethyl oxalate to water of 1:2; dissolve potassium ethyl oxalate in water to form a uniform solution, then add the first precursor, stir and mix at 30°C for 2h, and then dry at 105°C for 8h to obtain a precursor material containing potassium ethyl oxalate. Heat the precursor material containing potassium ethyl oxalate to 700°C at a heating rate of 3°C / min and keep it at a constant temperature for 4h for alkali activation, and discharge it after it cools naturally to room temperature; then add it to a 3mol / L acetic acid solution (the mass ratio of the alkali activated material to the acid solution is 1:2) and stir for 3h for acid washing. After filtering, wash the filter residue with ionized water until the solution is neutral to remove the residual potassium salt in the material, and finally dry it at 105°C for 8h to obtain the second precursor.

[0093] S3: The second precursor is placed in a box furnace, and under nitrogen protection, the temperature is first increased to 750°C at a rate of 3°C / min and kept at this temperature for 2 h, and then increased to 1300°C at a rate of 2°C / min and kept at this temperature for 4 h for high-temperature carbonization. After naturally cooling to room temperature, the third precursor is obtained.

[0094] S4: The third precursor is subjected to chemical vapor deposition in a rotary furnace, using methane as an organic carbon source with a methane ventilation rate of 50 mL / min, and nitrogen as a carrier gas with a nitrogen ventilation rate of 150 mL / min. The temperature is raised to a vapor deposition reaction temperature of 900°C at a heating rate of 3°C / min. The vapor deposition reaction time is 7 hours. After the reaction is completed, the material is discharged after naturally cooling to room temperature to obtain the hard carbon composite material.

[0095] Example 2

[0096] S0: 20kg of the purchased waste phenolic resin recycling (ash content is 0.8wt%, volatile content is 27wt%, residual carbon value is 68wt%) is crushed into particles of 3~5cm in size by a blade crusher, and then placed in an ultrasonic cleaning tank for ultrasonic cleaning. The ultrasonic cleaning power is 11000Hz, the ultrasonic cleaning water temperature is 55℃, and the cleaning time is 1h. After cleaning, it enters the convection drying system and is dried at 105℃ for 4h to obtain the waste phenolic resin.

[0097] S1: The waste phenolic resin obtained in S0 is placed in a drum furnace. Under nitrogen protection, the temperature is raised to 700°C at a rate of 3°C / min and kept constant for 3 h for pre-carbonization treatment. After the temperature naturally cools to room temperature, the material is discharged and then crushed by a jet mill to make D50 about 6μm to obtain the first precursor.

[0098] S2: Weigh potassium oxamate according to the mass ratio of the first precursor to the alkali compound of 1:0.8, and weigh water according to the mass ratio of potassium oxamate to water of 1:4; dissolve potassium oxamate in water to form a uniform solution, then add the first precursor, stir and mix at 30°C for 2h, and then dry at 105°C for 8h to obtain a precursor material containing potassium oxamate. The precursor material containing potassium oxamate is heated to 750°C at a heating rate of 4°C / min and kept at a constant temperature for 3h under nitrogen protection for alkali activation, and then discharged after naturally cooling to room temperature; then add it to a 3mol / L acetic acid solution (the mass ratio of the alkali activated material to the acid solution is 1:2) and stir for 3h for acid washing. After filtering, wash the filter residue with ionized water until the solution is neutral to remove the residual potassium salt in the material, and finally dry it at 105°C for 8h to obtain the second precursor.

[0099] S3: The second precursor is placed in a box furnace, and under nitrogen protection, the temperature is first increased to 800°C at a heating rate of 4°C / min and kept at this temperature for 3 h, and then increased to 1400°C at a heating rate of 1°C / min and kept at this temperature for 3 h for high-temperature carbonization. After naturally cooling to room temperature, the third precursor is obtained by discharging the material.

[0100] S4: The third precursor is subjected to chemical vapor deposition in a rotary furnace, using acetylene as an organic carbon source with a ventilation rate of 70 mL / min, nitrogen as a carrier gas with a ventilation rate of 150 mL / min, and the temperature is increased to a vapor deposition reaction temperature of 800°C at a heating rate of 2°C / min. The reaction time of vapor deposition is 8 h. After the reaction is completed, the material is discharged after naturally cooling to room temperature to obtain the hard carbon composite material.

[0101] Example 3

[0102] S0: 20kg of the purchased waste phenolic resin recycling (ash content is 0.8wt%, volatile content is 27wt%, residual carbon value is 68wt%) is crushed into particles of 3~5cm in size by a blade crusher, and then placed in an ultrasonic cleaning tank for ultrasonic cleaning. The ultrasonic cleaning power is 11000Hz, the ultrasonic cleaning water temperature is 55℃, and the cleaning time is 1h. After cleaning, it enters the convection drying system and is dried at 105℃ for 4h to obtain the waste phenolic resin.

[0103] S1: The waste phenolic resin obtained in S0 is placed in a drum furnace. Under nitrogen protection, the temperature is raised to 800°C at a heating rate of 2.5°C / min and kept at a constant temperature for 2 h for pre-carbonization treatment. After the temperature naturally cools to room temperature, the material is discharged and then crushed by a jet mill to make D50 about 6μm to obtain the first precursor.

[0104] S2: Weigh potassium bicarbonate according to the mass ratio of the first precursor to potassium bicarbonate of 1:1, and weigh water according to the mass ratio of potassium bicarbonate to water of 1:3; dissolve potassium bicarbonate in water to form a uniform solution, then add the first precursor, stir and mix at 30°C for 2h, and then dry at 105°C for 8h to obtain a precursor material containing potassium bicarbonate. The precursor material containing potassium bicarbonate is heated to 800°C at a heating rate of 3°C / min under nitrogen protection and kept at a constant temperature for 2h for alkali activation, and the material is discharged after it is naturally cooled to room temperature; then it is added to a 3mol / L acetic acid solution (the mass ratio of the alkali activated material to the acid solution is 1:2) and stirred for 3h for acid washing. After filtering, the filter residue is washed with ionized water until the solution is neutral to remove the residual potassium salt in the material, and finally dried at 105°C for 8h to obtain the second precursor.

[0105] S3: The second precursor is placed in a box furnace, and under nitrogen protection, the temperature is first increased to 700°C at a heating rate of 5°C / min and kept warm for 4 hours, and then increased to 1500°C at a heating rate of 3°C / min and kept warm for 2 hours for high-temperature carbonization. After naturally cooling to room temperature, the third precursor is obtained.

[0106] S4: The third precursor is subjected to chemical vapor deposition in a rotary furnace. The organic carbon source in this process is propane with a propane ventilation rate of 60 mL / min. The carrier gas is nitrogen with a nitrogen ventilation rate of 150 mL / min. The temperature is raised to a vapor deposition reaction temperature of 850°C at a heating rate of 2°C / min. The reaction time of vapor deposition is 6 hours. After the reaction is completed, the material is discharged after naturally cooling to room temperature to obtain the hard carbon composite material.

[0107] Example 4

[0108] S0: 20kg of the purchased waste phenolic resin recycling (ash content is 0.8wt%, volatile content is 27wt%, residual carbon value is 68wt%) is crushed into particles of 3~5cm in size by a blade crusher, and then placed in an ultrasonic cleaning tank for ultrasonic cleaning. The ultrasonic cleaning power is 11000Hz, the ultrasonic cleaning water temperature is 55℃, and the cleaning time is 1h. After cleaning, it enters the convection drying system and is dried at 105℃ for 4h to obtain the waste phenolic resin.

[0109] S1: The waste phenolic resin obtained in S0 is placed in a drum furnace. Under nitrogen protection, the temperature is raised to 750°C at a rate of 2°C / min and kept constant for 3 h for pre-carbonization treatment. The material is discharged after naturally cooling to room temperature. Then it is crushed by a jet mill to make D50 about 6μm to obtain the first precursor.

[0110] S2: Weigh potassium ethyl oxalate according to the mass ratio of the first precursor to potassium ethyl oxalate of 1:0.6, and weigh water according to the mass ratio of potassium ethyl oxalate to water of 1:5; dissolve potassium ethyl oxalate in water to form a uniform solution, then add the first precursor, stir and mix at 30°C for 2h, and then dry at 105°C for 8h to obtain a precursor material containing potassium ethyl oxalate. The precursor material containing potassium ethyl oxalate is heated to 750°C at a heating rate of 2°C / min under nitrogen protection and kept at a constant temperature for 4h for alkali activation, and then discharged after naturally cooling to room temperature; then add it to a 3mol / L acetic acid solution (the mass ratio of the alkali activated material to the acid solution is 1:2) and stir for 3h for acid washing. After filtering, wash the filter residue with ionized water until the solution is neutral to remove the residual potassium salt in the material, and finally dry it at 105°C for 8h to obtain the second precursor.

[0111] S3: The second precursor is placed in a box furnace, and under nitrogen protection, the temperature is first increased to 720°C at a heating rate of 2°C / min and kept warm for 4 h, and then increased to 1350°C at a heating rate of 2°C / min and kept warm for 3 h for high-temperature carbonization. After naturally cooling to room temperature, the third precursor is obtained.

[0112] S4: The third precursor is subjected to chemical vapor deposition in a rotary furnace. The organic carbon sources in this process are methane and acetylene, and the ventilation volume is 30 mL / min. The carrier gas is nitrogen, and the carrier gas ventilation volume is 140 mL / min. The temperature is increased to 950°C for vapor deposition at a heating rate of 5°C / min. The reaction time of vapor deposition is 5h. After the reaction is completed, the material is discharged after naturally cooling to room temperature to obtain the hard carbon composite material.

[0113] Example 5

[0114] S0: 20kg of the purchased waste phenolic resin recycling (ash content is 0.8wt%, volatile content is 27wt%, residual carbon value is 68wt%) is crushed into particles of 3~5cm in size by a blade crusher, and then placed in an ultrasonic cleaning tank for ultrasonic cleaning. The ultrasonic cleaning power is 11000Hz, the ultrasonic cleaning water temperature is 55℃, and the cleaning time is 1h. After cleaning, it enters the convection drying system and is dried at 105℃ for 4h to obtain the waste phenolic resin.

[0115] S1: The waste phenolic resin obtained in S0 is placed in a drum furnace. Under nitrogen protection, the temperature is raised to 800°C at a rate of 1.5°C / min and kept at a constant temperature for 2 h for pre-carbonization treatment. The material is discharged after naturally cooling to room temperature. Then it is crushed by a jet mill to make D50 about 6μm to obtain the first precursor.

[0116] S2: Weigh potassium oxamate according to the mass ratio of the first precursor to potassium oxamate of 1:0.5, and weigh water according to the mass ratio of potassium oxamate to water of 1:2; dissolve potassium oxamate in water to form a uniform solution, then add the first precursor, stir and mix at 30°C for 2h, and then dry at 105°C for 8h to obtain a precursor material containing potassium oxamate. The precursor material containing potassium oxamate is heated to 800°C at a heating rate of 1°C / min and kept at a constant temperature for 2h under nitrogen protection for alkali activation, and the material is discharged after it is naturally cooled to room temperature; then it is added to a 3mol / L acetic acid solution (the mass ratio of the alkali activated material to the acid solution is 1:2) and stirred for 3h for acid washing. After filtering, the filter residue is washed with ionized water until the solution is neutral to remove the residual potassium salt in the material, and finally dried at 105°C for 8h to obtain the second precursor.

[0117] S3: The second precursor is placed in a box furnace, and under nitrogen protection, the temperature is first increased to 680°C at a heating rate of 4°C / min and kept warm for 5 hours, and then increased to 1350°C at a heating rate of 2°C / min and kept warm for 4 hours for high-temperature carbonization. After naturally cooling to room temperature, the third precursor is obtained.

[0118] S4: The third precursor is subjected to chemical vapor deposition in a rotary furnace. The organic carbon source in this process is methane with a ventilation rate of 70 mL / min. The carrier gas is nitrogen with a ventilation rate of 150 mL / min. The temperature is raised to a vapor deposition reaction temperature of 850°C at a heating rate of 7°C / min. The reaction time of vapor deposition is 8 hours. After the reaction is completed, the material is discharged after naturally cooling to room temperature to obtain the hard carbon composite material.

[0119] Comparative Example 1

[0120] The difference between this comparative example and Example 1 is that the alkali activation step is not performed, but carbonization is performed directly, and the remaining steps are exactly the same as those in Example 1.

[0121] Comparative Example 2

[0122] The difference between this comparative example and Example 1 is that the chemical vapor deposition step is not performed, the product is the first precursor material, and the remaining steps are exactly the same as in Example 1.

[0123] Comparative Example 3

[0124] The difference between this comparative example and Example 1 is that no pre-carbonization step is performed, and chemical vapor deposition is directly performed on the alkali-activated material. The remaining steps are exactly the same as those in Example 1.

[0125] Comparative Example 4

[0126] The difference between this comparative example and Example 1 is that gas activation is adopted, and the remaining steps are exactly the same as those of Example 1. The specific steps are as follows:

[0127] S0: 20kg of the purchased waste phenolic resin recycling (ash content is 0.8wt%, volatile content is 27wt%, residual carbon value is 68wt%) is crushed into particles of 3~5cm in size by a blade crusher, and then placed in an ultrasonic cleaning tank for ultrasonic cleaning. The ultrasonic cleaning power is 11000Hz, the ultrasonic cleaning water temperature is 55℃, and the cleaning time is 1h. After cleaning, it enters the convection drying system and is dried at 105℃ for 4h to obtain the waste phenolic resin.

[0128] S1: The waste phenolic resin obtained in S0 is placed in a drum furnace. Under nitrogen protection, the temperature is raised to 650°C at a rate of 2°C / min and kept constant for 4 h for pre-carbonization treatment. The material is discharged after naturally cooling to room temperature. Then it is crushed by a jet mill to make D50 about 6μm to obtain the first precursor.

[0129] S2: The first precursor obtained in S1 is placed in an activation furnace, and under nitrogen protection, it is first heated to 900°C at a heating rate of 3°C / min, and then switched to carbon dioxide with a gas flow rate of 2L / min. After maintaining the temperature for 2h, the nitrogen is switched back, and the temperature is naturally cooled to room temperature before discharging to obtain the second precursor;

[0130] S3: The second precursor is placed in a box furnace, and under nitrogen protection, the temperature is first increased to 750°C at a rate of 3°C / min and kept at this temperature for 2 h, and then increased to 1300°C at a rate of 2°C / min and kept at this temperature for 4 h for high-temperature carbonization. After naturally cooling to room temperature, the third precursor is obtained.

[0131] S4: The third precursor is subjected to chemical vapor deposition in a rotary furnace, using methane as an organic carbon source with a methane ventilation rate of 50 mL / min, and nitrogen as a carrier gas with a nitrogen ventilation rate of 150 mL / min. The temperature is raised to a vapor deposition reaction temperature of 900°C at a heating rate of 3°C / min. The vapor deposition reaction time is 7 hours. After the reaction is completed, the material is discharged after naturally cooling to room temperature to obtain the hard carbon composite material.

[0132] Comparative Example 5

[0133] The difference between this comparative example and Example 1 is that pure phenolic resin (pure phenolic resin purchased from Hebei Zetian Chemical Co., Ltd., PF9182) is directly used as the raw material, and the remaining steps are exactly the same as those in Example 1.

[0134] Comparative Example 6

[0135] The difference between this comparative example and Example 1 is that the heating rate during the alkali activation process is 10° C. / min, and the other conditions are exactly the same as those in Example 1.

[0136] Comparative Example 7

[0137] The difference between this comparative example and Example 1 is that the pre-carbonization heating rate is 10° C. / min, and the other conditions are exactly the same as those in Example 1.

[0138] Effect Example 1

[0139] Characterization of specific surface area and pore structure: The specific surface area and pore structure of the material were determined using an American Micromeritics fully automatic adsorption-desorption instrument. The adsorbent for the specific surface area test was nitrogen, the measurement temperature was 77 K, and it was finally calculated by the BET method. The adsorbent for the micropore size test was carbon dioxide, the measurement temperature was 273 K, the powder degassing temperature was 300°C, and the relative pressure range P / P0 was 0-1, which was obtained by DFT model analysis.

[0140] According to the above method, Examples 1-5 and Comparative Examples 1-7 were tested. The relevant test results are shown in Tables 1 and Figure 1 shown.

[0141] Effect Example 2

[0142] 1. Material morphology characterization: A SEM image of the hard carbon material was obtained using a ZEISS scanning electron microscope. The SEM image of the hard carbon composite material obtained in Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the hard carbon composite material obtained in Example 1 of the present invention includes, from the inside to the outside, a core and a coating layer. Through further characterization, it can be found that the core contains a porous carbon material and the coating layer is a carbon layer.

[0143] 2. D50: The particle size D50 of the hard carbon negative electrode material was measured using Mastersize 2000 (Malvern 2000).

[0144] 3. True density: The true density of the hard carbon negative electrode material was measured using the American Quantachrome UltraPYC1200e fully automatic true density analyzer.

[0145] 4. Tap density: The tap density of the hard carbon negative electrode material was measured by tapping method using a tap density tester FZS4-4B.

[0146] The above test method was used to test Examples 1-5 and Comparative Examples 1-7. The relevant test results are shown in Table 1.

[0147] Effect Example 3

[0148] Electrochemical performance test: Take the hard carbon composite materials prepared in Examples 1-5 and Comparative Examples 1-7 respectively, weigh and grind them according to the mass ratio of negative electrode material to conductive agent and binder of 90:5:5, and use NMP as solvent to mix and prepare a viscous uniform slurry, and then use the doctor blade method to apply the slurry on the copper foil, and then put the coated copper foil into a vacuum oven at 80 ℃ and dry it for 12 hours. Cut the dried copper foil into 2 cm 2The working electrode was made of a disc. At room temperature, a metal sodium sheet was used as the negative electrode and the counter electrode, the electrode sheet prepared above was used as the working electrode, a GE-Whatman glass fiber diaphragm was used as the diaphragm, a 1 mol / L NaPF6 solution was used as the electrolyte, and the volume ratio of ethylene carbonate (EC) to dimethyl carbonate (DMC) was 1:1. CR2032 button cells were assembled in a vacuum glove box and tightly mechanically sealed. The assembled battery was left to stand at room temperature for 24 hours before the electrochemical test was started. Constant current charge and discharge experiments were carried out in the LAND battery test system, with a charge and discharge voltage window of 0~2.0 V and a charge and discharge rate of 0.1 C. The discharge capacity and first discharge efficiency of Examples 1-5 and Comparative Examples 1-7 were measured according to conventional test methods in the art, and the test results are shown in Table 1.

[0149] Table 1

[0150]

[0151] It can be seen from Examples 1-5 of the present invention that the present invention achieves effective regulation of relevant parameters such as the pore structure and specific surface area of ​​the hard carbon composite material through the synergistic effect between the various process steps, and the sodium ion battery made of the prepared hard carbon composite material as the negative electrode material has a high capacity and initial efficiency. Compared with Comparative Example 5 (directly using pure phenolic resin to prepare sodium ion batteries), the electrochemical performance of Examples 1-5 of the present invention is on par with it, and is significantly better than other comparative examples, which shows that the present invention achieves high-value recycling of waste phenolic resin and solves the problem of high cost of raw materials for negative electrode materials of sodium ion batteries.

[0152] Compared with the test results of Examples 1-5, although Comparative Example 1 has a higher initial efficiency, its sodium embedding capacity and reversible capacity are very low. This is because Comparative Example 1 has not been treated with alkali activation, and the hard carbon composite material prepared has a lower specific surface area than other examples, but without alkali activation etching, the hard carbon negative electrode intermediate cannot form a rich pore structure more effectively, and even after chemical vapor deposition, it cannot form a rich closed-pore structure, resulting in the inability to embed enough sodium, so its reversible capacity is relatively low.

[0153] Compared with the test results of Examples 1-5, Comparative Example 2 has a higher specific surface area and a relatively low first effect and reversible capacity. This is because Comparative Example 2 has not been coated with a chemical vapor deposition carbon source, the prepared hard carbon composite material has more defects, and more SEI films (i.e., interface films generated by the solid-liquid interface reaction between the electrolyte and the hard carbon material) are formed on the hard carbon surface, resulting in relatively low first effect and reversible capacity.

[0154] Compared with the test results of Examples 1-5, the reversible capacity and first coulombic efficiency of Comparative Example 3 are significantly reduced. This is because the alkali-activated material has more surface defects and pores without high-temperature carbonization treatment, and even after chemical vapor deposition treatment, all defects cannot be effectively coated.

[0155] Compared with the test results of Examples 1-5, the reversible capacity and the first coulombic efficiency of Comparative Example 4 are significantly reduced. This may be because the activation degree and effect of carbon dioxide activation (i.e., physical activation) are weaker than chemical activation (alkaline activation), and the closed-cell structure formed after subsequent treatment is less, resulting in lower reversible capacity and first efficiency of the battery.

[0156] The test results of Examples 1-5 are basically the same as those of Comparative Example 5, wherein the reversible capacity of Comparative Example 5 is lower. This may be because compared with pure phenolic resin, the recycled resin waste has other doping substances introduced during its early use, which is more conducive to the regulation of pore structure, and thus has a higher capacity.

[0157] Compared with the test results of Examples 1-5, the specific surface area after alkali activation of Comparative Example 6 is larger, and the reversible capacity and first efficiency are relatively poor. This is because the heating rate is too fast during the alkali activation process, the escape rate of small molecule gas is accelerated, the activation degree is deepened, and more effective pore structures cannot be formed.

[0158] Compared with the test results of Examples 1-5, the reversible capacity and first efficiency of Comparative Example 7 are relatively poor. This is because a faster heating rate will lead to incomplete volatile emission, affecting the effect of alkali activation, thereby affecting the formation of more effective pore structures. A lower heating rate means that the time to reach the pre-carbonization temperature will be longer, that is, within the same temperature range, on the one hand, the material will have more time to thermally decompose, making its volatile emission more thorough, and on the other hand, during the slow heating process, the resin molecules can also be further cured and cross-linked, which is beneficial to the subsequent regulation of the pore structure.

Claims

1. A method for preparing a hard carbon composite material, characterized in that: It includes the following steps: S1, heating the waste phenolic resin for pre-carbonization to obtain a first precursor; the heating rate is 1-4°C / min; S2. Under heating conditions, alkali-activating the first precursor to obtain a second precursor; the heating rate is 1-4°C / min; S3, carbonizing the second precursor to obtain a third precursor; S4. Carbon-coating the third precursor to obtain a hard carbon composite material.

2. The method for preparing the hard carbon composite material according to claim 1, characterized in that: Before pre-carbonization, it also includes: Step S0, crushing, washing and drying the waste phenolic resin recyclate to obtain the waste phenolic resin; Preferably, the waste phenolic resin recyclables are waste phenolic resin insulation boards; Preferably, the waste phenolic resin recyclate has at least one of the following parameters: ① ash content <2wt%; ② volatile matter <30wt%; ③ residual carbon value is 40-70wt%; Preferably, the cleaning is mechanical stirring cleaning or ultrasonic cleaning, preferably ultrasonic cleaning; further, the power range of the ultrasonic cleaning is 8000~14000Hz, preferably 11000Hz; further, the temperature range of the ultrasonic cleaning is 40~70℃, preferably 55℃; further, the time range of the ultrasonic cleaning is 0.5~3h, preferably 1h; Preferably, the drying method is convection drying and / or conduction drying, preferably convection drying; further, the temperature of the convection drying is 80-120°C, preferably 105°C; further, the time of the convection drying is 1-10h, preferably 3-8h, for example 4h.

3. The method for preparing the hard carbon composite material according to claim 1, characterized in that: In step S1, the D50 particle size of the first precursor is 3-10 μm, preferably 5-7 μm; And / or, in step S1, the particle size of the waste phenolic resin is 2 to 10 cm, preferably 3 to 5 cm; And / or, in step S1, the pre-carbonization temperature is 400-800°C, for example, 650°C, 700°C or 750°C; And / or, in step S1, the pre-carbonization time is 1 to 5 hours, such as 2 hours, 3 hours or 4 hours; And / or, in step S1, the heating rate is 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min; And / or, in step S1, the pre-carbonization is performed under an inert atmosphere; preferably, the inert atmosphere is argon or nitrogen, such as nitrogen; And / or, in step S1, the pre-carbonization equipment is a drum furnace, a box furnace, a rotary kiln or a pit furnace, such as a drum furnace; And / or, in step S1, a crushing step is further included after the pre-carbonization; preferably, the crushing equipment is a roller mill, a mechanical mill, a jet mill or a low-temperature mill, preferably a jet mill.

4. The method for preparing a hard carbon composite material according to claim 1, characterized in that: In step S2, the temperature of the alkali activation is 600-900°C, preferably 700-800°C, for example 750°C; And / or, in step S2, the alkali activation time is 1 to 5 hours, such as 2 hours, 3 hours or 4 hours; And / or, in step S2, the heating rate is 3°C / min; And / or, in step S2, the alkali activation operation includes: heating a precursor material comprising the first precursor and an alkali compound to perform alkali activation; Preferably, the alkaline compound is one or more of potassium bicarbonate, potassium ethyl oxalate, potassium oxamate and potassium hydrogen phosphate, for example, potassium ethyl oxalate, oxamate, potassium bicarbonate or potassium bicarbonate; Preferably, the mass ratio of the first precursor to the alkaline compound is 1:(0.1-1), for example, 1:0.5, 1:0.6 or 1:0.8; Preferably, the method for preparing the precursor material comprising the first precursor and the alkali compound comprises: mixing the alkali compound aqueous solution with the first precursor, stirring, and drying; Preferably, the mass ratio of the alkali compound to water in the alkali compound aqueous solution is 1:(1-10), preferably 1:(2-10), such as 1:2, 1:3, 1:4, 1:5; Preferably, the mixing temperature is 20-40°C, more preferably 25-35°C, for example 30°C; Preferably, the mixing time is 0.5 to 4 hours, more preferably 1 to 3 hours, for example 2 hours; Preferably, the drying temperature is 100-120°C, more preferably 100-110°C, for example 105°C; Preferably, the drying time is 2 to 12 hours, more preferably 4 to 10 hours, for example 8 hours; And / or, in step S2, the alkali activation is performed under an inert atmosphere; preferably, the inert atmosphere is a nitrogen atmosphere, an argon atmosphere or a helium atmosphere, for example, a nitrogen atmosphere.

5. The method for preparing the hard carbon composite material according to claim 1, characterized in that: In step S2, the alkali activation further includes a washing step; Preferably, the washing comprises acid washing and water washing steps in sequence; More preferably, the acidic solution used for the pickling is one or more of hydrochloric acid solution, phosphoric acid solution, nitric acid solution, sulfuric acid solution, acetic acid solution and formic acid solution, such as acetic acid solution; further, the concentration of the acidic solution is 0.5-6 mol / L, preferably 1-5 mol / L, such as 3 mol / L; more preferably, the stirring time of the pickling is 1-10 h, preferably 2-8 h, such as 3 h; More preferably, the washing is performed with deionized water until the solution is neutral; Preferably, the washing process further includes a drying step; more preferably, the drying temperature is 100-120°C, preferably 100-110°C, for example 105°C; more preferably, the drying time is 2-12h, preferably 4-10h, for example 8h.

6. The method for preparing a hard carbon composite material according to claim 1, characterized in that: In step S3, the carbonization is graded carbonization; Preferably, the graded carbonization includes a first carbonization and a second carbonization, the temperature of the first carbonization is 500-800° C., and the temperature of the second carbonization is 1100-1600° C.; Wherein, the temperature of the first carbonization is, for example, 680°C, 700°C or 720°C; Wherein, the temperature of the second carbonization is, for example, 1300° C., 1400° C. or 1500° C.; Wherein, the first carbonization holding time is preferably 1 to 6 hours, for example, 2 hours, 3 hours, 4 hours or 5 hours; Wherein, the second carbonization holding time is preferably 1 to 6 hours, such as 2 hours, 3 hours or 4 hours; Wherein, the heating rate of the first carbonization is preferably 2-10°C / min, such as 2°C / min, 3°C / min, 4°C / min or 5°C / min; Wherein, the heating rate of the second carbonization is preferably 1-10°C / min, such as 1°C / min, 2°C / min or 3°C / min; And / or, in step S3, the carbonization is performed under an inert atmosphere; preferably, the inert atmosphere is argon or nitrogen, such as nitrogen; And / or, in step S3, the carbonization equipment is a pit furnace, a rotary furnace, a tube furnace, a box furnace, a tunnel kiln, a vacuum furnace, a push plate kiln or a roller kiln, such as a box furnace.

7. The method for preparing a hard carbon composite material according to claim 1, characterized in that: In step S4, the carbon-coated carbon method is chemical vapor deposition; Preferably, the chemical vapor deposition method comprises the following steps: introducing an organic carbon source into a device containing the third precursor to perform a vapor deposition reaction; Preferably, the organic carbon source is one or more of n-hexane, cyclohexane, thiophene, acetylene, ethylene, propylene, methane and propane; Preferably, the gas flow rate of the organic carbon source is 5-100 mL / min, preferably 10-80 mL / min, such as 50 mL / min, 60 mL / min or 70 mL / min; Wherein, preferably, the carrier gas of the organic carbon source is argon and / or nitrogen, such as nitrogen; Preferably, the gas flow rate of the carrier gas of the organic carbon source is 20 to 500 mL / min, more preferably 50 to 300 mL / min, for example, 150 mL / min; Preferably, the reaction temperature of the vapor deposition reaction is 500-1000°C, preferably 650-950°C, for example 800°C, 850°C or 900°C; Preferably, the reaction time of the vapor deposition reaction is 4 to 15 hours, preferably 5 to 10 hours, for example 6 hours, 7 hours or 8 hours; Preferably, the heating rate of the vapor deposition reaction is 1-15°C / min, preferably 3-10°C / min, for example 5°C / min or 7°C / min; Preferably, the equipment used in the chemical vapor deposition method is a rotary furnace, a fluidized bed or a tubular furnace, such as a rotary furnace.

8. A hard carbon composite material, characterized in that It is prepared by the preparation method of the hard carbon composite material according to any one of claims 1 to 7; Preferably, the hard carbon composite material comprises, from inside to outside, a core and a coating layer; the core comprises a porous carbon material, and the coating layer is a carbon layer; Preferably, the specific surface area of ​​the hard carbon composite material is 1 to 10 m 2 / g, preferably 2~4 m 2 / g, for example 3.4 m 2 / g, 3.7 m 2 / g, 3.2 m 2 / g, 3.9 m 2 / g or 2.8m 2 / g; Preferably, the micropore diameter of the hard carbon composite material is 0.3-1.5 nm, preferably 0.4-1.0 nm, such as 0.53 nm, 0.75 nm or 0.83 nm.

9. Use of the hard carbon composite material as claimed in claim 8 as an electrode material in a battery.

10. A battery, characterized in that: The battery comprises the hard carbon composite material according to claim 8.

Citation Information

Patent Citations

  • Porous carbon material based on epoxy resin recycled from waste and preparation method and application of porous carbon material

    CN113321201A

  • Novel biomass hard carbon sodium-ion battery material and preparation method thereof

    CN115353090A

  • Preparation method of sodium ion battery negative electrode material based on resin precursor

    CN116374991A

  • Hard carbon negative electrode material for sodium ion battery and preparation method of hard carbon negative electrode material

    CN117049504A

  • Method for preparing hard carbon negative electrode by using waste ion exchange resin

    CN117228654A

Cited By

  • Spherical porous carbon, silicon-carbon composite material, preparation method and application of spherical porous carbon and silicon-carbon composite material, and battery

    CN120483148A